2013
DOI: 10.1590/s0102-86502013001100004
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia and reperfusion of rat small intestine using pentoxyfilline and prostaglandin E1

Abstract: PURPOSE:To investigate the small intestinal tissue alterations in rats submitted to ischemia and tissue reperfusion using pentoxyfilline or prostaglandin E1. METHODS:Thirty five Wistar rats were used, distributed into group control (A) n=10 were submitted to intestinal ischemia and reperfusion during 60 minutes and no one drug have been utilized. In the group pentoxyfilline (B) n=10 have been utilized during tissue ischemia and reperfusion as well as prostaglandin E1 (C) n=10, but separately . In the group sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…In the IR-PTX group, we found that the villi were well preserved, the leukocytes were less conspicuous, and the capillaries were dilated. Corroborating our findings, previous reports described more severe villous lesions in animals subjected to IR without any treatment compared to animals subjected to PTX treatment 13,17,18,[22][23][24][25] . Other reports using PTX at concentrations less than or equal to the concentrations used in this study have reported the preservation of the villi in the intestinal epithelium, similar to the results described here 13,17,18,[22][23][24][25][26] .…”
Section: ■ Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the IR-PTX group, we found that the villi were well preserved, the leukocytes were less conspicuous, and the capillaries were dilated. Corroborating our findings, previous reports described more severe villous lesions in animals subjected to IR without any treatment compared to animals subjected to PTX treatment 13,17,18,[22][23][24][25] . Other reports using PTX at concentrations less than or equal to the concentrations used in this study have reported the preservation of the villi in the intestinal epithelium, similar to the results described here 13,17,18,[22][23][24][25][26] .…”
Section: ■ Discussionsupporting
confidence: 90%
“…The discovery that PTX had an anti-TNF-α effect stimulated its application into organ ischemia 13,14,19,[21][22][23] . PTX is a nonselective phosphodiesterase inhibitor 12,14,18,19 that decreases TNF-alpha and NFkB gene transcription 13,14,19 , affecting multiple steps in the cytokine/chemokine pathways and exerting beneficial immunomodulatory effects on inflammatory conditions directly and indirectly 12,13,[21][22][23][24][25][26][27] . PTX increased the levels of specific cytokines, increased cyclic adenosine monophosphate (cAMP) levels and decreased TNF-alpha levels, resulting in anti-inflammatory and antioxidant properties 12,18,21,23,25,26 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…16 demonstrated that PTX and PGE1, separately administered to different groups, attenuated intestinal mucosa lesions caused by tissue ischemia-reperfusion 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The animals in GA were subjected to 60 min ischemia followed by 60 min reperfusion (as described in the next topic), but were given no test drugs 13 ; GB animals underwent ischemia and reperfusion with PTX at 40 mg kg -1 distributed as 20 mg kg -1 given 3 min before the beginning of ischemia and 20 mg kg -1 given 3 min before reperfusion; GC animals underwent ischemia and reperfusion with PGE1 at 5 μg kg -1 distributed as 2.5 μg kg -1 given 3 min before the beginning of ischemia and 2.5 μg kg -1 given 3 min before reperfusion; GD animals (sham group) were subjected to all experimental procedures-i.e., analgesia, anesthesia, and laparotomy-except clamping of the mesenteric artery or drug use.…”
Section: The Research Was Approved By the Committee For Ethics In Resmentioning
confidence: 99%
“…Pentoxifylline is a derivative of xanthine, which decreases blood viscosity by increasing deformability of red blood cells and is used to symptomatic relief of intermittent thrombosis,14 and its usage has been effective in therapy of cardiovascular diseases, cerebrovascular diseases, other diseases related to local blood flow abnormalities (vascular),1516 and reduction of ischemic effects 17. Common side effects of using pentoxifylline are nausea, vomiting, headache, dizziness, and rare complications such as angina, arrhythmias, shortness of breath, and hypotension.…”
Section: Introductionmentioning
confidence: 99%